Mechanically robust triboelectric nanogenerator with a shear thickening fluid for impact monitoring. Issue 19 (29th April 2022) - Yun, Seong-Yun; Tcho, Il-Woong; Kim, Weon-Guk; Kim, Do-Wan; Son, Joon-Ha; Lee, Sang-Won; Choi, Yang-Kyu
Abstract : A triboelectric nanogenerator using a shear thickening fluid is fabricated. Its Janus-face behaviors are analyzed by comparative experiments. With its enhanced mechanical robustness and durability, an impact monitoring system is developed. Abstract : As interest in wearable electronics continues to increase, a triboelectric nanogenerator (TENG) which uses a conductive liquid as a single electrode has attracted considerable attention. Even though a liquid-based TENG is attractive for power supply to drive a wearable device due to its intrinsic shape-adaptability, a mechanical weakness is problematic. To improve its weak mechanical robustness, here, a TENG was developed using a shear thickening fluid (STF-TENG) that has the Janus-face property of a solid and a liquid. It is composed of an eco-friendly material: water, corn starch, salt (NaCl), which is preferable for an 'appropriate technology'. The viscosity of the shear thickening fluid increases as the shear rate increases. The unique behaviours of the STF-TENG were compared to two control TENGs, composed of a conventional liquid and a solid electrode, respectively, and analyzed in terms of a shear thickening effect (STE). Unlike the two control TENGs, the electrical output of the STF-TENG varied according to the applied shear rate. In detail, the STF-TENG takes advantage of a larger contact area at a low shear rate produced by low velocity applied pressure, and a greater contact force at a high shear rate produced by high velocity applied pressure. The STF-TENG showed an inherent impact-absorbing property, which was evaluated using a metal ball dropped from various heights. After a durability test of 102 600 cycles of contact–separation, the output voltage of the STF-TENG did not decrease. Its mechanical robustness was confirmed by a stabbing experiment with a pointed gimlet. Thus, the proposed STF-TENG can protect a human body from strong impact while simultaneously harvesting biomechanical energy. These distinctive features can be favourably utilized as a multi-functional sensor without the need for an external power supply such as a battery. As a practical application, the STF-TENG was demonstrated as an impact monitoring system linked to a smartphone to provide a warning when a strong impulse was applied to the human body.